Variability in endocrine cell identity in patients with chronic pancreatitis undergoing islet autotransplantation. Issue 5 (28th November 2018) - Beamish, Christine A.; Gaber, A. Osama; Afshar, Solmaz F.; Fraga, Daniel W.; Hamilton, Dale J.; Sabek, Omaima M.
Abstract : Beta‐cell dedifferentiation as shown by cellular colocalization of insulin with glucagon and/or vimentin, and decreased expression of MAFA and/or urocortin3 has been suggested to contribute to metabolic decompensation in type 2 diabetes, and was recently described postimplantation in islet allotransplant patients. Dysglycaemia and diabetes mellitus are often encountered preoperatively in patients undergoing pancreatectomy and islet autotransplantation (PIAT). In this series of case reports, we document variation in islet phenotypic identity in three patients with chronic pancreatitis (CP) without diabetes or significant insulin resistance who subsequently underwent PIAT. Pancreas histology was examined using colocalization of endocrine hormones, mesenchymal and pan‐endocrine markers in islets, and the relative expression of MAFA and urocortin3 in insulin‐expressing cells as compared to that of nondiabetic and type 2 diabetic donors. We present results of pre‐ and posttransplant clinical metabolic testing. Varying degrees of islet‐cell dedifferentiation are identified in nondiabetic patients with CP at the time of PIAT, and may need further investigation. Abstract : This study reports islet dedifferentiation in patients with chronic pancreatitis without established diabetes.